SPORTS PHYSIOTHERAPY: MAPPING OF INJURY REGIONS IN REGULAR CROSSFIT PARTICIPANTS LINKED TO TWO BOXES IN THE CITY OF FOZ DO IGUAÇU/PR (Fiep Bulletin - online, 2024)
Introduction: Crossfit is a workout session designed to benefit overall physical conditioning and improve health. The practice of this modality involves performing certain exercises that, if done incorrectly, can lead to musculoskeletal injuries. Sports physiotherapy aims to restore the athlete’s functional health for sports practice.. Objective: To map the most frequent injuries related to the profiles of Crossfit practitioners regularly associated with two boxes in the city of Foz do Iguaçu/PR.. Methods: This is an observational, cross-sectional, and quantitative study conducted in two Crossfit boxes located in the city of Foz do Iguaçu/PR. Two unified questionnaires were used in this research, aiming to observe the athletes' profiles, types of injuries, and injured areas due to sports practice.. Results: A mapping of the most frequent injuries related to the profiles of practitioners from two high-performance Crossfit boxes was carried out, thus providing an understanding of what can be done to prevent injuries in athletes regularly linked to these gyms. It was observed that the majority of people affected by injuries were female and attended Crossfit Vila A Conclusion: This study allowed the analysis of the frequency and location of physical injuries that affect Crossfit athletes in the city of Foz do Iguaçu. Finally, it is noteworthy that this study has limitations, considering that it was carried out in a specific sociodemographic, cultural, and economic reality.